The Constitutional Perspective of Indonesian Social Security System - Saut Parulian Panjaitan; Joni Emirson; Iza Rumesten RS; Suci Flambonita (Jurnal Hukum, 2024)
Some of the values contained in the regulation of the National Social Security System Law (SJSN) and the Social Security Management Agency Law (BPJS) are contrary to constitutional values. The purpose of this paper is to examine the conflict of values. The study was conducted using normative legal research methods, which focused on the statutory and theoretical approach. This study found that social welfare mandated by the 1945 Constitution to the state is developed through the national social security system: (a) as an obligation, (b) to empower the weak and incapable people to develop themselves in accordance with human dignity, and (c) in order to fulfill basic needs, both the right to education, the right to health, and the right to get a job. In addition, although the 1945 Constitution does not specify the pattern of the social security system to be developed, the SJSN Law and the BPJS Law use a mixed model between social insurance from participants and social assistance from the state to the poor. Based on this, it is recommended to adjust the formulation of legal norms of the SJSN Law and BPJS Law contained with constitutional values.